Effectiveness of Macroprudential Policies in Developing Asia: An Empirical Analysis - Minsoo Lee; Ruben Carlo Asuncion; Jungsuk Kim (Asian Development Bank (ADB), 2015)
The global financial crisis highlighted the need for national bank supervisory authorities to improve surveillance systems and to detect early on the buildup of macroeconomic risks that could threaten the entire financial system. This paper presents an empirical framework for analyzing how effective macroprudential policies control credit growth, leverage growth, and housing price appreciation. Two significant findings emerge. Broadly, macroprudential policies can indeed promote financial stability in Asia. More specifically, different types of macroprudential policies are more effective against different types of macroeconomic risks.
hdl:11540/5078
Keywords: G01; G28; L51; 330; developing Asia; financial stability; macroprudential policy